СИСТЕМА РАЗВИТИЯ И СОВЕРШЕНСТВОВАНИЯ ОСНОВНЫХ КОМПОНЕНТОВ КОМПЕТЕНТНОСТНОГО ПОДХОДА - Жалилов, О.М. (SCIENCE and SOCIETY, 2023)
Development of foreign language competences of future foreign language teachers on the basis of a person-oriented approach, improvement of the system of training foreign language teachers through information educational technologies, scientifically based improvement of technologies that diagnose the level of development of foreign language skills in pedagogues from the perspective of a competent approach are of great importance.